Akurasi Google Earth Dalam Pengukuran Arah Kiblat - Zainul Arifin (Universitas Cokroaminoto Yogyakarta, 2017)
Google Earth is one of the technologies of computer programs that provide facilities for the user to see the buildings in three dimensions, providing a latitude and longitude information of places around the globe. The purpose of using Google Earth to measure the direction of Qibla is to analyze and determine the measurement accuracy of Google Earth in the direction of Qibla, outlining the steps Google Earth in the measurement of the direction of Qibla. In this case the method of field research, testing experimental approach by comparison tools theodolite, measuring the direction of Qibla with Google Earth was conducted in three big buildings are: Masjid Agung Jawa Tengah, Masjid Kauman Yogyakarta, Masjid Ulil Albab UII Yogyakarta. Three small buildings are At-Tauba Mosque, al-Ikhlas Mosque, an-Nur mosque in Beringin Semarang.